Methods for Patient-Centered Interface Design of Test Result Display in Online Portals. Issue 1 (26th June 2018) - Nystrom, Daniel T.; Singh, Hardeep; Baldwin, Jessica; Sittig, Dean F.; Giardina, Traber D.
Objectives: Patients have unique information needs to help them interpret and make decisions about laboratory test results they receive on web-based portals. However, current portals are not designed in a patient-centered way and little is known on how best to harness patients' information needs to inform user-centered interface design of portals. We designed a patient-facing laboratory test result interface prototype based on requirement elicitation research and used a mixed-methods approach to evaluate this interface. Methods: After designing an initial test result display prototype, we used multiple evaluation methods, including focus group review sessions, expert consultation, and user testing, to make iterative design changes. For the user testing component, we recruited 14 patient-users to collect and analyze three types of data: comments made during testing sessions, responses to post-session questionnaires, and system usability scores. Results: Our initial patient-centered interface design included visual ranges of laboratory values, nontechnical descriptions of the test and result, and access to features to help patients interpret and make decisions about their results. Findings from our evaluation resulted in 6 design iterations of the interface. Results from user testing indicate that the later versions of the interface fulfilled patient's information needs, were perceived as usable, and provided access to information and techniques that facilitated patient's ability to derive meaning from each test result. Conclusions: Requirement elicitation studies can inform the design of a patient-facing test result interface, but considerable user-centered design efforts are necessary to create an interface that patients find useful. To promote patient engagement, health information technology designers and developers can use similar approaches to enhance user-centered software design in patient portals.